Challenges faced by secondary school teachers in integrating computers in English language classrooms in the Samarahan and Kuching districts - Prisca, anak Ugus. (Universiti Malaysia Sarawak, UNIMAS, 2008)
This study identified the challenges faced by secondary school teachers in integrating computer s in English language classroom s around the Samarahan and Kuching District s and investigates the factors that contribute d to such challenges. A ques tionnaire consist ing of 20 items about the challenges faced by the teacher s were administered to a group of 100 teachers from 12 secondary schools around the Samarahan and Kuching District s. A semi - structured interview was also conducted to investigate th e factors that contribute d to such challenges. There were 6 semi - structured questions for the respondents to answer during the interview sessions. For this purpose, 12 respondents were chosen randomly to represent the target population. The questionnair es are analyzed by using the statistical analysis and the semi - structured interview was analyzed qualitatively. The findings and discussions appeared to show that availability which is 74% was the most challenges faced by the teacher in integrating comput er, followed by 65% challenges due to time constraint, 49% challenges in teaching preparation, 24% challenges due to technical problems, next 15% challenges due to the teachers attitude and motivation and lastly, lack of technology skills that is 14% was t he least challenges. Factors have been identified to be the causes to the challenges faced. The main factors are the limited number of computers, laptops, LCD and computer lab in school.